Let m and n be the two roots of the equation x 2 + a x + b = 0 , where a and b are constants. If the two roots of x 2 − b x + a = 0 are m + 1 4 and n + 1 4 , what is the value of a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
H e r e , m a n d n b e t h e r o o t s o f e q u a t i o n x 2 + a x + b = 0 S o , m = 2 − a + a 2 − 4 b = > 2 m = − a + a 2 − 4 b a n d n = 2 − a − a 2 − 4 b = > 2 n = − a + a 2 − 4 b H e n c e , 2 m + 2 n = − 2 a = > m + n = − a − − − − − − − − − ( i ) A g a i n , m + 1 4 a n d n + 1 4 b e t h e r o o t s o f e q u a t i o n x 2 − b x + a = 0 S o , m + 1 4 = 2 − ( − b ) + b 2 − 4 a = > 2 ( m + 1 4 ) = b + b 2 − 4 a a n d n + 1 4 = 2 − ( − b ) − b 2 − 4 a = > 2 ( n + 1 4 ) = b − b 2 − 4 a H e n c e , 2 ( m + n + 1 4 + 1 4 ) = 2 b = > m + n + 2 8 = b − − − − − − − − − − ( i i ) N o w , E q u a t i o n ( i i ) − E q u a t i o n ( i ) b − ( − a ) = m + n + 2 8 − m − n = > a + b = 2 8 S o , v a l u e o f a + b = 2 8 ( A n s w e r ) .
Problem Loading...
Note Loading...
Set Loading...
The simpler way is to use Viète's relations. So, for the equation x^2+ax+b=0, the sum of the roots is m+n = -a (1) and for the equation x^2-bx+a=0, the sum is m+n+28=b (2). From (1) and (2) => 28-a=b => a+b=28